Digital Pedagogical Resources as Supportive Aids for Children with Autism Spectrum Disorder - Dr. Michael F. Brynt; Dr. Henrik L. Olsen (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2025)
Autism Spectrum Disorder (ASD) presents diverse educational challenges stemming from its core characteristics in social communication, interaction, and repetitive behaviors. This article explores the efficacy of digital pedagogical resources as assistive technologies for children with ASD. Through a qualitative review of existing literature and an examination of a specific case study (Squizzy application), it investigates various forms of educational software, including mobile applications, augmented reality (AR) tools, and AI-powered robotics, and their applications in enhancing social skills, communication, and academic outcomes. The findings highlight the significant benefits of these technologies in providing individualized, visually-driven, and engaging learning experiences that can supplement traditional therapeutic approaches. The discussion also addresses critical considerations such as the quality and suitability of available software, the complex issue of generalizing learned skills to real-world contexts, prevailing issues of access and equity, and the indispensable role of human intervention and supervision. The article concludes that while these digital tools hold immense potential to foster development and inclusion for children with ASD, their effective and responsible implementation requires careful selection, thoughtful integration into broader intervention strategies, and ongoing research to maximize their long-term impact and address current limitations.